(untitled) (The Pakistan Development Review, 2004)
This study examines the health status of Pakistani children using two important indicators, morbidity and malnutrition measured by weight-for-age and height-for-age. The demand for medical services has also been determined. The main data source used in this study is the 2000-01 Pakistan Social-Economic Survey (PSES), which provides sufficient information on child health and poverty. Findings of the study show that both exclusive breastfeeding during the first 4-5 months of life and immunisation can help control the occurrence of illness significantly among the young children (0-5 months). These also reinforce the role of mother’s education in the production of child health (nutritional status). This role of mother’s education is found to be more pronounced in the poor families than in the non-poor families. The rise in poverty since the mid-1990s has adversely influenced the nutritional status of children. The basic issue is about how to reduce the household food insecurity. The benefits of recent high GDP growth may be transferred to the poor through employment generation, which has been slow in the past decade. Real incomes of the poor and the vulnerable segments of the population may also be protected against the rise in prices of essential food items. At present, the health and nutrition sector is getting only 0.7 percent of the GDP. Health care facilities in the country are curative in nature, and are heavily skewed in favour of the diagnostic and treatment side, not preventive healthcare aspects. More resources should be made available for preventive healthcare aspects. Coverage of child immunisation should be enhanced, and the provision of safe drinkingwater may be given high priority in the social sector policies.